Enhanced fitness of a Bactrocera cucurbitae genetic sexing strain based on the addition of gut‐isolated probiotics (Enterobacter spec.) to the larval diet. Issue 2 (February 2017) - Yao, Mingyan; Zhang, Hehe; Cai, Pumo; Gu, Xiaohong; Wang, Dan; Ji, Qinge
Abstract: The melon fruit fly, Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae), is polyphagous and an important fruit and vegetable pest. Sterile insect technique (SIT) is a 'hot' research field for pest control, particularly in fruit flies. A B. cucurbitae genetic sexing strain (GSS) was established for SIT. Mass rearing and superior‐fit target species are crucial components of SIT. Some reports have demonstrated that the irradiation used for SIT damages the midgut and tissues of target species, which can impair SIT success. Other studies have found that probiotics in the fruit fly larval diet can enhance host fitness. We used culture‐based approaches to isolate and characterize gut‐associated bacterial species from the B. cucurbitae GSS during mass rearing and applied one of the isolated bacteria, Enterobacter spec., as a probiotic mixed into the larval diet to examine its effect on B. cucurbitae . The results indicate that pupal weight, survival rate, and some morphological indices were significantly increased.